Understanding the Molecular Mechanism(s) of SARS-CoV2 Infection and Propagation in Human to Discover Potential Preventive and Therapeutic Approach - Raj, Sibi; Chandel, Vaishali; Rathi, Brijesh; Kumar, Dhruv (Coronaviruses, 2020)
Exported across the world might create a serious controversy. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection into the host undergoes a huge number of complex replicative machineries which remains unclear. Understanding the mechanism (s) of replication and mode of infection of SARS-CoV2 to human cells will help us in the development of novel vaccines or drugs for the eradication and prevention of the disease. This review compiles the knowledge of SARS-CoV2 replicative machinery, mode of infection to the human cells and the development of drugs and vaccines which are currently under clinical trials.
Keywords: COVID-19